Development of Australian Aboriginal Drama: the journey towards kullark (home) - Polak, Iva (Array, 2009)
This paper traces the development of Australian Aboriginal drama from the late 1960s to the 1990s. Aboriginal playwrights initially started writing engaged plays out of necessity of their current socio-historical conditions. However, plays by Aboriginal authors such as Kevin Gilbert, Robert Merrit and Gerald Bostock that appeared in the late 1960s and early 1970s indicated that Aboriginal drama would become a forum for rewriting history of Australia. The turning point is the appearance of Jack Davis in the late 1970s, who still remains the most important Aboriginal playwright of all times. His plays challenge official historical records and attempt to fill in numerous historical ellipses by evoking Aboriginal counter-memory. Moreover, Davis is the first Aboriginal author in general to introduce vibrancy of Aboriginal languages in indigenous cultural production. His legacy continues in the next generations of playwrights appearing in the late 1980s such as Eva Johnson and Richard Walley. The next shift in Aboriginal drama occurs in 1991 with the publication of Bran Nue Dae: A Musical Journey by Jimmy Chi. This carnivalesque play constructs a possible multicultural Australia offering an unequivocally happy ending to the nation, revealing that reconciliation lies in cultural diversity and not in cultural difference.